Features of Poltava Region Sustainable Recreational System Development in the Territory Branding Context - Borodych, Larysa; Koniuk, Andrii; Savchenko, Oleksandr; Vasyliev, Pavlo (International Journal of Engineering and Technology, 2018)
The analysis of territory branding factors that is the driving force for the development of the recreational and health-improving system of the Poltava region is carried out. It was concluded that the urban construction concept is the initial impulse of the territorial branding strategy. The approaches used by the regions to create their brand strategy are analyzed. As a result of the analysis of the structure of urban planning, to identify common factors that affect both the design of urban development objects and the design of the brand territory. It is concluded that the urban construction concept is the starting impulse of the territorial branding strategy. The types of potentially attractive resources for economic development and the increase of attractiveness of the region are determined. On the example of the Novosanzhar settlement council, explored the potential for branding of territories in the context of improving economic growth, the competitiveness of the locality and the development of health-improving tourism on the basis of sustainable development principles.Â